2018
DOI: 10.1007/s00438-018-1465-y
|View full text |Cite
|
Sign up to set email alerts
|

LaMIR166a-mediated auxin biosynthesis and signalling affect somatic embryogenesis in Larix leptolepis

Abstract: Somatic embryogenesis (SE) involves complex molecular signalling pathways. Understanding molecular mechanism of SE in Larix leptolepis (L. leptolepis) can aid research on genetic improvement of gymnosperms. Previously, we obtained five LaMIR166a (miR166a precursor) -overexpression embryonic cell lines in the gymnosperm Larix leptolepis. The proliferation rates of pro-embryogenic masses in transgenic and wild-type lines were calculated. Overexpression of the miR166a precursor LaMIR166a led to slower proliferati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 40 publications
2
9
0
Order By: Relevance
“…Additionally, REV function is necessary for polar auxin transport in the shoot[83]. Li et al[51,84,85] demonstrated that over-expression of LaMIR166a and down-regulated of LaHDZIP31-34 genes results in different IAA levels in pro-embryogenic masses of L. leptolepis . The authors speculated that LaMIR166 targeted HD-ZIP III genes likely regulate auxin biosynthesis and response genes.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, REV function is necessary for polar auxin transport in the shoot[83]. Li et al[51,84,85] demonstrated that over-expression of LaMIR166a and down-regulated of LaHDZIP31-34 genes results in different IAA levels in pro-embryogenic masses of L. leptolepis . The authors speculated that LaMIR166 targeted HD-ZIP III genes likely regulate auxin biosynthesis and response genes.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, REV function is necessary for polar auxin transport in the shoot [79]. Li et al [45,80,81] demonstrated that over-expression of La-miR166a and down-regulated of LaHD-ZIP31-34 genes results in different IAA levels in pro-embryogenic masses of L. leptolepis. The authors speculated that La-miR166 targeted HD-ZIP III genes likely regulate auxin biosynthesis and response genes.…”
Section: Plos Onementioning
confidence: 99%
“…Wild embryogenic cultures were obtained from L. kaempferi immature zygotic embryos on the induction medium, LaMIR166a was cloned into a psuper1300+ binary vector and successfully transformed into embryogenic suspensor masses (ESMs), and five transgenic embryogenic cell lines were obtained, which increased lateral root number and biomass at the germination stage [19][20][21]. Based on our previous studies, we selected three of these soft and fresh cell clusters (named a-3, a-4, and a-5), which were grown for 20 days on the proliferation medium at the same developmental stage; they were cultured in triplicate and taken from different culture masses.…”
Section: Plant Materialsmentioning
confidence: 99%
“…Previous studies have found that LaMIR166a may indirectly regulate the development of SAM by affecting WOX expression [19]. LaMIR166a plays an important role in auxin biosynthesis and signal transmission during somatic embryo maturation and germination [20,21]. However, the role of miR166 and its regulatory mechanisms in the proembryo stage are not clear.…”
Section: Introductionmentioning
confidence: 99%